Cysteine as an Innovative Biomarker for Kidney Injury - Woo, Hye Young; An, Jong Min; Park, Min Young; Han, Ahram; Kim, Youngwoong; Kang, Jisoo; Ahn, Sanghyun; Min, Seung-Kee; Ha, Jongwon; Kim, Dokyoung; Min, Snagil (Lippincott Williams & Wilkins Ltd., 2025)
Background. Kidney transplantation is a widely used treatment for end-stage kidney disease. Nevertheless, the incidence of acute kidney injury (AKI) in deceased donors poses a potential hazard because it significantly increases the risk of delayed graft function and potentially exerts an influence on the kidney allograft outcome. It is crucial to develop a diagnostic model capable of assessing the existence and severity of AKI in renal grafts. However, no suitable kidney injury markers have been developed thus far. Methods.？ We evaluated the efficacy of the molecular probe NPO-B, which selectively responds to cysteine, as a new diagnostic tool for kidney injury. We used an in vitro model using ischemia/reperfusion injury human kidney-2 cells and an in vivo ischemia/reperfusion injury mouse model. Additionally, cysteine was investigated using urine samples from deceased donors and living donors to assess the applicability of detection techniques to humans. Results.？ This study confirmed that the NPO-B probe effectively identified and visualized the severity of kidney injury by detecting cysteine in both in vitro and in vivo models. We observed that the fluorescence intensity of urine samples measured using NPO-B from the deceased donors who are at a high risk of renal injury was significantly stronger than that of the living donors. Conclusions.？ If implemented in clinical practice, this new diagnostic tool using NPO-B can potentially enhance the success rate of kidney transplantation by accurately determining the extent of AKI in renal grafts.